Romantic migrations, refused migrations. The search for cross-border marriages between Spanish men and Latin American and Slavic women - Roca Girona, Jordi (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
The article focuses on an emerging kind of migration, the so called «migration for love», detected in the 90’s. This phenomenon takes place in a global society on the basis of the transformation of both, gender patterns and the love concept. This issue deals with individual women who individually plan their migration (what we call «dependant incorporation») and with the denial of the migratory condition, which entails, in most cases, the absence of any return plans
Keywords: Romantic migration/Migration by love; cross-border marriages